The Prevalence of Iron Deficiency Anemia in Primary Antiphospholipid Syndrome - Karin KLACK,; Vanessa MONMA,; Karina PELIÇARI,; Simone APPENZELLER,; Jozélio Freire de CARVALHO3, (Archives of Rheumatology, 2013)
Objectives: The aim of this study was to evaluate the prevalence of subclinical and clinical iron deficiency with iron deficiency anemia in primary antiphospholipid syndrome (PAPS). Patients and methods: The study was comprised of 29 PAPS patients and 29 healthy controls matched for age, gender, and socioeconomic status. Participants received iron, folic acid, vitamin B12, and vitamin C. A battery of tests was performed to determine the iron storage. The mean disease duration was 70±51.3 months in the patient group. Results: Iron storage depletion was observed in 10.3% of the individuals in both groups (p=0.5). Iron deficient erythropoiesis (IDE) was observed in only three PAPS patients (10.3%) (p<0.001). Iron deficiency anemia (IDA) was more common in the PAPS patients compared to controls (48.2% vs. 10.3%, respectively; p=0.009). The mean iron levels were significantly lower in the PAPS group than the controls (75.5 vs. 95.8, respectively; p=0.03). Red cell distribution width-coefficient of variation (RDW-CV) (14.9 vs. 13.2; p=0.02) and red cell distribution widthstandard deviation (RDW-SD) (46.7 vs. 40.5; p=0.009) were significantly increased in the patient group. The folic acid and vitamin C levels were lower in the PAPS group than the control group (p<0.05). Conclusion: This study showed for the first time that PAPS patients have a higher incidence of IDA and IDE compared to healthy controls. This can be attributed to inadequate ingestion of folic acid and vitamin C.